2018
DOI: 10.3390/ijgi7070250
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Point Cloud Acquisition of Unknown Indoor Scenes

Abstract: This paper presents a methodology for the automatic selection of heuristic scanning positions in unknown indoor environments. The surveying is carried out by a robotic system following a stop-and-go procedure. Starting with a random scan position in the room, the point cloud is discretized in voxels and they are submitted to a two-step classification and are labelled as occupied, occluded, empty, window, door, or exterior based on a visibility analysis. The main objective of the methodology is to obtain a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…After the visibility analysis, voxels are classified into: 'visible' and 'occluded'. A voxel is considered 'occupied' if it contains a minimum number of 20 points as in (González-deSantos et al, 2018). Figure 8 shows the results in terms of three-dimensional representation of space view accomplished for Test A (central visual angle, and mid-peripheral visual angle).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…After the visibility analysis, voxels are classified into: 'visible' and 'occluded'. A voxel is considered 'occupied' if it contains a minimum number of 20 points as in (González-deSantos et al, 2018). Figure 8 shows the results in terms of three-dimensional representation of space view accomplished for Test A (central visual angle, and mid-peripheral visual angle).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…This UGV has a payload of 50kg and an autonomy of three hours. Similar systems have been previously used for this purpose [ 23 , 24 , 27 ]. This UGV makes use of SLAM algorithms for autonomous navigation, thus this manuscript will focus on NBV calculation.…”
Section: Methodsmentioning
confidence: 99%
“…This grid is treated like an image, using a pattern to look for rectangular holes that may be a door/window, using the method presented by González-de Santos et al . [ 27 ]. For this study case only rectangular windows are considered, for other types of windows, such as circular or oval windows it would be necessary to define different patterns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next scan position is chosen according to the probabilities calculated in the previous step. González-de Santos et al [30] extend previous approaches to also consider windows and doors, which are identified through a visibility analysis. In this way, once acquisition is completed for one room, the existence of doors determines subsequent next best scans.…”
Section: Scan-planning In Indoor Environmentsmentioning
confidence: 99%